Interparental conflict and adolescents' self-representations: the role of emotional insecurity - Silva, C. S.; Calheiros, M. M.; Carvalho, H. (Journal of Adolescence, 2016)
Adolescents' signs of emotional insecurity in the context of interparental conflict (IC) – emotional reactivity, internal representations (i.e., constructive/destructive; spillover) and behavioral responses (i.e., withdrawal; inhibition; involvement) – were examined as mediators in the relation between IC and adolescents' self-representations. Self-reported measures were filled out by 221 Portuguese adolescents (59.3% girls; Mage = 12.91), attending public elementary and secondary schools. IC predicted less favorable self-representations. Adolescents' emotional reactivity and withdrawal mediated the relation between IC and emotional and physical appearance self-representations, while conflict spillover representations and constructive family representations mediated associations between IC and instrumental self-representations. This study emphasizes the importance of interparental conflict and adolescent emotional insecurity in the construction of their self-representations, having important theoretical and practical implications. It highlights the value of analyzing the specific role of several emotional insecurity dimensions, and informs practitioners' work aimed at promoting constructive conflict and adaptive emotional regulation skills.